PELATIHAN PEMBUATAN ALAT PERAGA EDUKATIF DARI SAMPAH DALAM MENCIPTAKAN PEMBELAJARAN EFEKTIF PADA SISWA SEKOLAH DASAR DI DESA MUARA TELUKNAGA TANGERANG - Sukirno Hadi Raharjo; Achmad Anwar Abidin; Memet Casmat; Ichwan Ichwan; Suhartono Suhartono (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
This community service program aims to increase teachers' creativity in using and utilizing educational teaching aids (ETA) made from recycled goods. Carried out in Muara Village, Teluknaga District, Tangerang Regency, the service method uses the Participatory Action Research (PAR) approach. This program takes place with three main stages: planning starting from research, implementation that directly involves teachers, and evaluation. In addition to training on making ETA, this activity also includes education on waste sorting for ETA materials and recycling. The results showed an increase in teachers' ability to make and use ETA and an increase in students' interest in learning. This article also summarizes the stages of the program, the impact felt by partners, and development steps for its sustainability.